Ibm Pelatihan Membuat Laporan Penjualan dengan Menggunakan Spreadsheet pada Guru Muhammadiyah Adiwerna Kabupaten Tegal - Ida Farida; Sunandar Sunandar; Aryanto Aryanto; Reza Cesar Tiarso; Winda Wulandari (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2021)
The development of technology and information systems in the industrialized world requires an agency to be able to use technology to support industrial operations. Computer accounting is one of the areas of information technology (IT) which is supported by the ability and mastery in accounting, where computers are used as technology to run applications used in processing accounting transactions as well as to produce financial reports of a company. Vocational High Schools or SMK have an important role in preparing and developing Human Resources. Spreadsheet is a number processing program that has various advantages, namely, it is easy to process data faster, it is easy to calculate data, helps in calculating data, makes it easier to complete numerical tasks. Vocational High School of Muhammadiyah Adiwerna since implementing the 2013 curriculum, requires training related to spreadsheets. SMK Muhamadiyah Adiwerna which has a vocational accounting program must equip teachers with knowledge and mastery of accounting programs, especially the Spreadsheet application program, considering that currently spreadsheets have been used by thousands of small, medium and large scale companies in Indonesia and abroad.